PENGARUH KOMPETENSI PEDAGOGIK GURU DAN FASILITAS BELAJAR SEKOLAH TERHADAP PRESTASI BELAJAR SISWA SMK N 1 MOTOLING TIMUR - Tiwow, Gilly; Wuisang, Jerry; Ranti, Devyano; Sumangkut, Luis (Jurusan Pendidikan Ekonomi Fakultas Ekonomi dan Bisnis UNIMA, 2025)
This study aims to determine the effect of Pedagogical Competence and School Learning Facilities on Student Learning Achievement at SMK Negeri 1 Motoling Timur. This study uses three variables, namely (X1) Pedagogical Competence variable, Learning Facilities (X2) and Student Learning Achievement (Y). Where (X1) and (X2) Using a questionnaire given to 50 students who are members of the class XI student population of SMK Negeri 1 Motoling Timur. The questionnaire uses a Likert scale with 15 questions, each alternative answer choice has a different score. While (Y) is measured using the report card results. The results of the Regression Equation are: Y = 56.76 + 0.28X1 + 0.16X2, this shows that there is an influence between pedagogical competence and learning facilities on student learning achievement, meaning that every 1 unit increase in the pedagogical competence and learning facilities variables will increase student learning achievement by. Keywords: Pedagogical Competence, Learning Facilities, Student Learning Achievement.